Towards an Ethics of Autism : A Philosophical Exploration. - Hens, Kristien. (Open Book Publishers, 2021)
What does it mean to say that someone is autistic?Towards an Ethics of Autism is an exploration of this question and many more. In this thoughtful, wide-ranging book, Kristien Hens examines a number of perspectives on autism, including psychiatric, biological, and philosophical, to consider different ways of thinking about autism, as well as its meanings to those who experience it, those who diagnose it, and those who research it. Hens delves into the history of autism and its roots in the work of Leo Kanner and Hans Asperger to inform a contemporary ethical analysis of the models we use to understand autism today. She explores the various impacts of a diagnosis on autistic people and their families, the relevance of disability studies, the need to include autistic people fully in discussions about (and research on) autism, and the significance of epigenetics to future work on autism.